Financial Crisis, Labour Markets and Institutions. - Fadda, Sebastiano (Routledge frontiers of political economy., 2013)
This book seeks to explain the global financial crisis and its wider economic, political, and social repercussions, arguing that the 2007-9 meltdown was in fact a systemic crisis of the capitalist system. The volume makes these points through the exploration of several key questions:What kind of institutional political economy is appropriate to explain crisis periods and failures of crisis-management? Are different varieties of capitalism more or less crisis-prone, and can the global financial crisis can be attributed to one variety more than othe.